Penggunaan Media Pembelajaran dengan Benda Konkret untuk Meningkatkan Kemampuan Berhitung pada Peserta Didik Kelas II SDN 187 - Agrini, Maihelya; Agustin, Firdia Tri (YASIN, 2023)
Learning is the interaction of students with educators, and learning resources in the learning environment, teachers, students and infrastructure are very important factors. In learning, teachers must create a comfortable learning atmosphere and innovative and fun learning models. However, there are still many problems in learning Mathematics which of course makes students' interest in learning low. This research aims to explore the numeracy skills of Class II students at SDN 187 Teratai. The approach used in this research is a quantitative approach with a Classroom Action Research (PTK) design. The research subjects were class II students at SDN 187 Teratai, totaling 13 students with 5 male students and 8 female students. Meanwhile, there is only 1 class II teacher. Data collection in research uses test and non-test instruments. The non-test consists of observation, documentation and interviews with teachers who teach in class II at SDN 187 Teratai. The data obtained was then analyzed using the stages of data reduction, data description and data verification. The research results showed that students' mathematics learning outcomes had increased by 25%, namely from 60% to 85%. This shows that using concrete object media can improve learning outcomes on entertainment themes for class II students at SD N 187/I Teratai.